Strategi Barter Kolaborasi dengan Influencer untuk Promosi Pariwisata Smartway Tours - Revinda Mauliatiz Zahroh Hakiki; Nurudin (KOMUNIKA, 2026)
The paradigm shift toward Society 5.0 demands tourism promotion strategies that are authentic and capable of addressing cost-related challenges. This study analyzes the implementation and effectiveness of influencer collaboration through barter as an adaptive promotional model. Using a descriptive qualitative approach with source triangulation through interviews, observations, and documented studies, the findings show that influencer selection prioritizes value fit and authentic storytelling quality over quantitative metrics as the initial screening. This model is sustained through a rational exchange in which brands gain cash-flow optimization, visibility, and credibility, while influencers gain experience and long-term credibility maintenance. This strategy has proven effective in generating curiosity and producing strategic lead generation at the Middle of the Funnel (MOFU), ultimately supporting conversions.